Recurrent Fistula between Ileal Pouch and Vagina—Successful Treatment with a Gracilis Muscle Flap - Feride Aydin; Claus Ferdinand Eisenberger; Andreas Raffel; Alexander Rehders; Stefan Benedikt Hosch; Wolfram Trudo Knoefel (Case Reports in Medicine)
Fistulae between an ileal pouch and the vagina are an uncommon complication of ileal pouch-anal anastomosis following proctocolectomy and mucosectomy in patients with familial adenomatous polyposis coli. Several reports describe the successful use of muscle flaps to close recurrent pouch-vaginal-fistulae (PVF). However, series only contain small numbers and an optimal management has not yet been determined. We report the case of a 26-year old woman with a third recurrence of a PVF after proctocolectomy for treatment of familial adenomatous polyposis in October 2005. Because local approaches failed, definitive closure of the fistula was achieved by interposition of a gracilis muscle flap between the pouch-anal anastomosis and the vagina. The postoperative course was uneventful; the patient was discharged 7 days after surgery and remained free of recurrence and symptomatic complaints for 22 months now. The gracilis muscle flap proved to be an effective method in the treatment of recurrent PVF.